A review article on the role of Kusthadi Lepa in Ek-Kustha (Psoriasis) - Aswal, Sakshi; Gupta, Arvind; Barmola, Roopali (International Research Journal of Ayurveda & Yoga, 2025)
All skin disease comes under the umbrella of Kustha Roga. Ek-Kustha is one among the Kshudra Kustha with the dominancy of Vata and Kapha Doshas. It is characterized by symptoms of Aswedanam, Mahavastu, and Matsyashakalopam. It resembles Psoriasis, which is an autoimmune and chronic inflammatory dermatosis characterized by erythematous plaques and silvery scales predominantly affecting the skin of the elbow, scalp, and knees. Currently, the modern medical science treats psoriasis with synthetic drugs, i.e., methotrexate, Psoralen ultraviolet light A, Vitamin D3 lotion, and steroid creams. Hence, there is a need for a treatment having safe and has good efficacy. Acharya Charak mentioned that the treatment of Ek-Kustha by external medications, i.e., Takradhara, Lepa, Udhavartan, Pradeha, etc., are effective in Ek-Kustha. Therefore, in this article, an attempt was made to aim the role of Kusthadi Lepam in Ek-Kustha (Psoriasis).